Optic nerve head: A gatekeeper for vitreous infectious insults? - Lai, Wenwen; Huang, Jie; Fang, Wangyi; Deng, Saiyue; Xie, Yi; Wang, Wei; Qiao, Tong; Xu, Gezhi; Wang, Xiaowei; Ding, Fengfei (Frontiers in Immunology, 2022)
The axons of retinal ganglia cells (RGCs) pass through the optic nerve head (ONH) and form the optic nerve (ON). The ONH behaves as an anatomical interface between vitreous cavity and subarachnoid space. After acute neuroinflammation induced by intravitreal injection of lipopolysaccharides (LPS), inflammatory activation was evident in retina. However, we did not detect signs of inflammation in posterior ONH and infiltrating inflammatory cells in ONH. Therefore, we hypothesized that ONH could barrier the vitreous inflammation. With transmission electron microscopy, we identified mild but evident demyelination in the posterior ON on day 7 post intravitreal injection (PII) of LPS as compared with PBS group. With confocal imaging of ex vivo tissue extracted from Aldh1L1-eGFP reporter mice, we observed the ONH astrocytes alter their spatial orientation by elongating cell morphology along the axonal axis of RGCs in LPS- versus PBS-treated eyes, which was quantified by the increased ratio of longitudinal (DL) and transverse (DT) diameter of astrocytes and the proportion of longitudinally locating astrocytes. We further conducted RNA sequencing of ONH on day 1 PII and found drastic upregulation of pathways involving inflammation and immune reactions. Gene set enrichment analysis (GSEA) revealed that LPS-induced transcriptomic alterations were significantly enriched in astrocyte and microglia cell type-specific gene sets. Herein, we report that the vitreous infectious insults induce morphological changes of ONH astrocytic and transcriptomic alterations enriched in cell types of astrocyte and microglia. Glial activation in ONH could defend the vitreous infectious insults and barrier inflammation penetration into the central nervous system.